Textile Characterization for Wearable Antenna Application Using Transmission Line Method - Md. Pazil, Anis Fariza; Abd Rahman, Nurul Huda; Ramli, Nurulazlina; Awang, Robi'atun Adayiah; Abdul Aziz, Noor Hafizah (International Journal of Integrated Engineering, 2023)
This proposed work introduces the textile characterisation analysis based on the effects of fabric thickness and dielectric properties using the transmission line method for a wearable textile antenna. The return loss (S11) and transmission loss (S21) were analysed for denim, felt and Tencel in correlation with the conductivity properties using Computer Simulation Technology with Rogers 5880 as the reference sample. By varying the fabric thickness from 0.5 mm to 4 mm, the optimum thickness and type of fabric can be identified from the S11 and S21 parameters. In the transmission line simulation, the sample-under-test is a stripline with the conductivity values from 10-2 to 108 S/m. Results are further plotted against the thicknesses to observe the behaviour of all three textiles samples. The results show that Felt substrate with 3 mm thickness give the best performance. The felt substrate demonstrates the best transmission performance judging from the lowest transmission loss due to the low tangent loss followed by Tencel and denim. For accuracy analysis, the actual and calculated conductivity were also presented to show the textiles performance at low and high region of conductivity. The study reveals the importance of choosing the correct substrate with suitable dielectric and electrical properties before being implemented into the antenna design for good efficiency.